Peran Kepala Sekolah sebagai Manajer Pendidikan dalam Menumbuhkan Semangat Kebangsaan Melalui Pendidikan Kewarganegaraan (PKn) - Iswiyanto, Hendra Ani (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
The principal has a strategic role in shaping the national character of students through effective education management. This study aims to examine how the principal carries out his managerial function in supporting Pancasila and Citizenship Education (PKn) learning as an effort to foster a spirit of friendship in the school environment. The research method uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The data analysis technique uses Milles & Huberman's data analysis technique through three stages, namely: Data condensation, data display, and data verification. The study results indicate that the principal plays a role in planning, organizing, implementing, and evaluating PPKn learning programs oriented towards strengthening nationalism values. The strategies used include strengthening the climate, developing extracurricular activities, creating a nationalist school climate, and partnerships with external communities. The implications of these findings indicate the importance of principal leadership in building a young generation that has a strong national identity.